Subperiosteal drainage versus subdural drainage in the management of chronic subdural hematoma (a comparative study) - Ng Wei Chih, Adrian (2015)

(untitled)
Symptomatic chronic subdural hematomas (csdh) remain one of the most frequent diagnoses in current neurosurgical practice. With the aging population especially in the well-developed and developing countries, the incidence of csdhs is expected to steadily witness an exponential rise. Burr-hole craniostomy with irrigation and placement of a close-system drainage is the current recommended surgery for symptomatic csdh. The aim of this study is to perform a direct comparison between two surgical techniques in the treatment of symptomatic csdh, which have been proven in previous studies to be efficient. Our main objective was to compare the efficacy of placement of a subperiosteal drain (spd) and a subdural drain (sdd) following single burr-hole craniostomy and irrigation, and also to demonstrate any significant differences in terms of overall surgical complications, functional outcome at 3 months and mortality rate. The study was carried out in two well established local neurosurgical centres, whereby the spd group was performed in hospital umum sarawak (hus) and the sdd group was performed in hospital sultanah aminah johor bahru. Our study spanned over a duration of 2 years with data of 30 patients for both groups colleted and analyzed. Overall, there were no statistically significant difference in terms of patient general characteristics, pre-operative and post-operative symptoms, markwalder grades on admission and at discharge, post-operative hematoma volume and recurrence, mortality and functional outcome at discharge and at 3 month follow-up between both groups of patients. Although not achieving statistical significance, we observed a lower rate of surgical complication especially for post-operative intracranial hematoma with placement of the spd system. This study concludes that treatment with single burr-hole craniostomy, irrigation and placement of spd system is equally effective to the sdd system with a lower overall surgical complication rate for csdhs. Subperiosteal drainage versus subdural drainage in the management of chronic subdural hematoma (a comparative study)